2022
DOI: 10.3390/s22228684
|View full text |Cite
|
Sign up to set email alerts
|

Core Synergies Measured with Ultrasound in Subjects with Chronic Non-Specific Low Back Pain and Healthy Subjects: A Systematic Review

Abstract: Low back pain represents the leading cause of disability since 1990. In 90% of cases, it is classified as non-specific low back pain, being chronic in 10% of subjects. Ultrasound has proven to be an effective measurement tool to observe changes in the activity and morphology of the abdominal muscles. This article reviews which core synergies are studied with ultrasound in healthy subjects and with chronic non-specific low back pain. A systematic review was conducted on studies analyzing synergies between two o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Working together, they generate lumbopelvic forces that enhance trunk stability, control, and effective movement. Additionally, this coordinated effort improves balance, coordination, postural stability, and alignment while also supporting continence 11 , 12 . Research conducted by Hides et al 39 revealed an improvement in the multifidus muscle’s cross-sectional area following a stabilization training program that targeted the PFMs in conjunction with training the multifidus and abdominal muscles in young elite cricketers experiencing low back pain, confirming the synergistic interaction among these muscles.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Working together, they generate lumbopelvic forces that enhance trunk stability, control, and effective movement. Additionally, this coordinated effort improves balance, coordination, postural stability, and alignment while also supporting continence 11 , 12 . Research conducted by Hides et al 39 revealed an improvement in the multifidus muscle’s cross-sectional area following a stabilization training program that targeted the PFMs in conjunction with training the multifidus and abdominal muscles in young elite cricketers experiencing low back pain, confirming the synergistic interaction among these muscles.…”
Section: Discussionmentioning
confidence: 98%
“…The PFMs are among the primary core muscles, alongside the diaphragmatic, transversus abdominis, and lumbar multifidus muscles. The interplay of the aforementioned muscles forms a cylindrical structure that collaborates to generate forces within the lumbopelvic region, leading to enhanced stability and control of the trunk, fostered movement effectiveness, better balance, harmonized coordination, heightened postural alignment and stability, as well as maintenance of continence 11 , 12 . Despite this synergistic action between the PFMs and other core muscles, current rehabilitation programs for VL focus on PFM training 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The practical application of our results is limited to the three muscles that were examined and cannot be extended to other muscles, such as the quadriceps and other trunk muscles. The change in muscle thickness observed through ultrasound provides an indication of muscle size and contraction during exercise [ 61 ]. Therefore, our results cannot be directly compared to similar studies conducted with electromyography or MRI.…”
Section: Discussionmentioning
confidence: 99%
“…These myofascial muscles work together to create a corset-like system with balanced tension [ 38 ]. Synergistic effects between the core muscles have been reported in systematic reviews [ 39 ]. Increased thickness during the transversus abdominis muscle contraction has been shown in healthy participants after an invasive intervention on the lumbar multifidus muscle [ 40 ].…”
Section: Discussionmentioning
confidence: 99%